Getting the Neutrality of Village Heads and Village Devices in General Elections: - Rusliandy Rusliandy (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The practical problem that arises is the existence of a village head/village apparatus in charge of a political party or has committed violations in the Presidential/Vice Presidential elections, Regional Head elections, legislative / DPD elections, and even violations of village head elections. The method used literature review, which is accomplished by compiling articles from newspapers or web media related to the Neutrality of the Village Head and Village Officials. The results showed that the village head/village apparatus had a mass base in the area, so it was often used to support or participate in elections. On the other hand, the village head/village apparatus also strives to carry out practical politics to get closer to and get more attention from regional heads, political party elites or the Central Government in budget allocations or financial or development assistance for their regions. There was also pressure, intimidation or promises directed at the village head to commit a neutrality violation. To achieve neutrality for village heads/village officials, it is necessary to increase Regional Heads, Heads of Service and District Heads in fostering and supervising village government through socialization and prosecution for those who commit violations. It is also necessary to formulate regulations regarding a code of ethics for village heads/village officials to control. Regional heads, career officials and related officials must also provide an example by being neutral during the election.